Lung metastasis following temporary discontinuation of lenvatinib and tislelizumab in hepatocellular carcinoma: A case report - Wang, Chen-Dong; Liu, Run-Dong; Liu, Ming-Jie; Song, Jia (World journal of gastrointestinal surgery, 2025)
BACKGROUND Hepatocellular carcinoma (HCC) is a prevalent malignancy in China, primarily diagnosed at advanced stages, which limits treatment options and increases mortality rates. Conversion therapy, which includes systemic and locoregional treatments, aims to render unresectable tumors resectable. Nonetheless, research is scant on the risks of disease progression during the temporary cessation of targeted drugs and immune checkpoint inhibitors before surgery. CASE SUMMARY This report describes a 58-year-old male with HCC who developed lung metastases following the discontinuation of lenvatinib and tislelizumab, revealing the necessity for further investigation into the management of HCC patients during the perioperative period, particularly concerning the timing and duration of targeted therapy and immunotherapy. CONCLUSION Our study highlights the complex challenges in managing advanced HCC and emphasizes the critical need for ongoing research to refine treatment strategies and improve patient outcomes.